Ultra-thin lithium aluminate spinel ferrite films with perpendicular magnetic anisotropy and low damping - Xin Yu Zheng; Sanyum Channa; Lauren J. Riddiford; Jacob J. Wisser; Krishnamurthy Mahalingam; Cynthia T. Bowers; Michael E. McConney; Alpha T. N’Diaye; Arturas Vailionis; Egecan Cogulu; Haowen Ren; Zbigniew Galazka; et al. (Nature Communications, 2023)
Abstract Ultra-thin films of low damping ferromagnetic insulators with perpendicular magnetic anisotropy have been identified as critical to advancing spin-based electronics by significantly reducing the threshold for current-induced magnetization switching while enabling new types of hybrid structures or devices. Here, we have developed a new class of ultra-thin spinel structure Li0.5Al1.0Fe1.5O4 (LAFO) films on MgGa2O4 (MGO) substrates with: 1) perpendicular magnetic anisotropy; 2) low magnetic damping and 3) the absence of degraded or magnetic dead layers. These films have been integrated with epitaxial Pt spin source layers to demonstrate record low magnetization switching currents and high spin-orbit torque efficiencies. These LAFO films on MGO thus combine all of the desirable properties of ferromagnetic insulators with perpendicular magnetic anisotropy, opening new possibilities for spin based electronics.